The Effect of Fetal Liver-derived Cell Suspension Allotransplantation on Patients with Wolfram Syndrome: the First Year of Follow-up - Ensieh NASLI ESFAHANI; Maryam GHODSI; Ali TOOTEE; Camelia RAMBOD; Bagher LARIJANI; Akbar SOLTANI (Tehran University of Medical Sciences, 2015)
Background: Cell therapy has emerged as a promising curative intervention for several diseases including diabetes and Wolfram Syndrome (WS). The current study aimed to assess the effectiveness of clinical application of fetal-liver derived stem cells for treatment of patients with WS. Methods: Six patients with WS aged 23-34 (mean: 29.50, SD: 4.76) were recruited for the current phase 3 single-arm clinical trial. The participants underwent fetal liver-derived hematopoietic stem cell transplantation. In order to evaluate the effectiveness of transplantation, glycemic control indexes were measured at regular follow-up sessions. Results: One patient (out of six) experienced a 6 months insulin-free period with acceptable HbA1c levels. In another patient with history of recurrent hypoglycemic attacks, the frequency of bout of attacks remarkably decreased. There was no significant change in other patients. Conclusion: Stem-cell therapy may represent a new method for treatment of patients with Wolfram Syndrome.   Keywords: Stem Cell, Allotransplantation, Wolfram Syndrome, Diabetes